Information Needs of Patients About Immunosuppressive Medication in a German Kidney Transplant Sample: Prevalence and Correlates - Klewitz, Felix; Nöhre, Mariel; Bauer-Hohmann, Maximilian; Tegtbur, Uwe; Schiffer, Lena; Pape, Lars; Schiffer, Mario; de Zwaan, Martina (Frontiers in Psychiatry, 2019)
Worldwide clinical guidelines for the care of kidney transplant (KT) recipients recognize the importance of health care providers imparting appropriate immunosuppressive medication (ISM) information for the facilitation of safe medication self-management. The extent of medication information made available is, however, not necessarily what patients require to know about their prescribed medicines. A useful indicator for determining the quality of prescription practice is to what degree the provided information meets the personal needs of patients. No previous studies have focused on the ISM information needs of KT patients. This study aims to investigate how satisfied KT patients are with the provided ISM information and to examine the association between satisfaction levels and socio-demographic, psychosocial, and transplant-related variables. KT patients (n=440) were asked to complete a series of self-report questionnaires to evaluate the variables adherence, ISM experience, perceived social support, symptoms of anxiety, and depression, and transplant-related information (i.a. donation type). ISM information needs were assessed with the Satisfaction with Information about Medicines Scale (SIMS-D). On average, 35.9% of the answers to the SIMS-D items indicated dissatisfaction with the received information; dissatisfaction was more prevalent for the SIMS-D subscale “potential problems” (46.1%) than the SIMS-D subscale “action and usage” (26.7%). On an individual item level the dissatisfaction with information concerning ISM side effects on drowsiness (57.1%) and sex life (56.3%) was most notable. Higher satisfaction with ISM information was correlated with higher age, better adherence, higher perceived social support and lower anxiety levels. Multiple linear regression analyses revealed that adherence, perceived social support and age were independently associated with ISM information satisfaction. No associations were found with sex, educational level, partnership status, symptoms of depression, experience of side effects and transplant-related variables. The data indicate that a substantial proportion of KT patients have unmet ISM information needs, especially with regard to potential problems of ISM. Dissatisfaction with ISM information is a potential amendable risk factor for KT patients engaging in non-adherent behavior, thus justifying further research in this area. ISM information should be tailored to meet the individual needs of KT patients in order to promote optimal medication self-management and adherence behavior.